Integration of small economies in the Free Trade Area of the Americas - Bernal, Richard L. (CSIS Americas Program WashingtonUS, 1998)
Examines the question of defining a small economy and discusses the implications of small size for economic growth and participation in trade arrangements with larger economies. Makes recommendations on how the interests and concerns of small economies can be incorporated into the design of the Free Trade Area of the Americas.